Optimizing Residential Energy Efficiency Through Strategic Landscaping in Hot-Arid Regions - Aldersoni, Ali (International Journal of Architectural Engineering Technology, 2025)
The Kingdom of Saudi Arabia (KSA) has a hot and arid climate, with the maximum summer temperature above 50°C. This high temperature can significantly hinder energy generation and usage since air conditioning is extensively used during the summer and is the primary cause of energy consumption. These researchers have to develop innovative solutions to overcome the above issues, as these would help decrease energy usage and improve the microclimate. In this study, the researchers have determined the efficiency of having green spaces to improve outdoor thermal comfort and decrease energy consumption in residential complexes that were developed by KSA’s Ministry of Housing (M.o.H). For this purpose, they have used a hybrid model that combined field data analysis and simulation modelling techniques to determine the effect of strategic landscaping on the microclimate and subsequent energy consumption. Their study showed that the integration of green spaces leads to a 3% decrease in annual energy consumption. The results noted in this study implied that the above interventions could improve thermal comfort in hot and arid conditions as they decreased the outdoor temperatures by 1.5°C and increased relative humidity in the area by 10% during the major summer months. The findings highlight how planned landscaping can help address environmental and energy challenges in areas with extreme climates.